Women as shari’ah court judges: Malaysia and Indonesia - Wan Muhammad, Ramizah (2018)
Woman and shari'ah court has been discussed in many literature works for a long time. There are juristic views on the eligibility of a woman to hold the post of a judgeship in Islamic judiciary in which the majority of the Muslim jurists who opined that they are not qualified enough to hold the post and others say that they qualified but subject to certain and limited jurisdictions. As a result of the juristic views there are also fatwas about the permissibility and non-permissibility of a woman to hold a post of shari'ah court judge including in Malaysia. Despite the non-unanimous decision on this issue there are some states in Malaysia such as Selangor and Federal Territories which have appointed a woman to be a judge. Comparing this issue with Indonesia including Aceh, one could see that Indonesia is in the forefront in acknowledging woman in the Islamic judiciary. The paper is an attempt to see how this issue being dealt with among these two countries by looking into the related laws governing the qualifications of a judge and the challenges that a woman judge faces in the two countries